Synthesis and Characterization of Tripositive Metal Ions Catechol Siderophore Complexes - Ibrahim, M.; Farooq, T.; Imran, M.; Rehmani, F.S.; Gulzar, T.; Shafique, A.A.; Shafique, A.; Aslam, M. (Asian Journal of Chemistry, 2013)
Over the past few years, siderophore desferrioxamine mesylate has been used for the treatment of iron overload. It is a linear trihydroxamate, a natural siderophore produced by streptomyces and employed to remove the extra iron contents from human body. In deed, catechol is a simple model of catechol type siderophore. So, taking it as an advantage, catechol was used for complexation with tripositive metal ions like Al(III), Cr(III) and Fe(III) with emphasis on their availability in biological environments/systems. Further, these catechol complexes were studied by potentiometric titrations and thermodynamic stability and stability constants were calculated by using BEST® software. Moreover, competitive reactions were performed to evaluate the ability of tripositive metal ions to replace Fe(III) which is widely found in biological system.